Optimal Monetary Policy in a Simple Distorted Economy - Massimiliano Marzo (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2004)
In this paper I search for an optimal configurations of parameters for variants of the Taylor rule by using an Accurate Second-Order Welfare based method within a fully microfounded Dynamic Stochastic model, with price rigidities, without capital accu- mulation. Money is inserted via a transaction cost function, price rigidities are modelled via quadratic cost of price adjustment. A version of the model with distortionary taxation is also explicitly tested. The model is solved up to Second Order solution. Optimal rules are obtained by maximizing a conditional welfare measure, differently from what has been done in the current literature. Optimal monetary policy functions turn out to be characterized by inflation targeting parameter lower than in empirical studies. In general, the optimal values for moentary policy parameters depend from the degree of nominal rigidities and from the role of fiscal policy. When nominal rigidities are higher, optimal monetary policy becomes more aggressive towards inflation. With a tigther fiscal policy, optimal monetary policy turns out to be less inflation-aggressive. Moreover, the results show that relying conditional welfare mea- sure avoids the problems related with first-order or unconditional welfare measures. Impulse Response functions based on second order model solution show a non-a ne pattern when the economy is hit by shocks of different magnitude.
Keywords: 330; Geldpolitik; Regelbindung versus Diskretion; Taylor-Regel; Inflationssteuerung; Preisrigidität; Finanzpolitik; Theorie; USA